PENGARUH KUALITAS PELAYANAN, KEPUASAN, DAN KEPERCAYAAN MEREK TERHADAP NIAT PEMBELIAN ULANG DI TOKO ONLINE TOKOPEDIA - Masitoh, Martina Rahmawati; Wibowo, Hermansyah Andi; Sunaryo, Deni (Jurnal Manajemen, 2018)
Online business in Indonesia is growing very rapidly nowadays. Repurchase intention in online business becomes the variable that determines the continuity of online business even to win the competition. Various scientific literature shows several factors that determine the high level of repurchase intentions such as service quality, customer satisfaction and trust.The purpose of this study was to examine the indirect effect of service quality on repurchase intentions mediated by customer satisfaction and brand trust.Sampling method in this research is purposive sampling.The survey was conducted by distributing questionnaires directly to Tokopedia online store customers in Banten. The number of samples 202 customers.Data analysis techniques using Structural Equation Model (SEM) with LISREL software.The SEM estimation results show that the research model used is in accordance with the empirical data that has been collected. The results of this study proves that the quality of service has a positive and significant impact on customer satisfaction. Consumer satisfaction has a positive and significant impact on brand trust. Brand trust has a positive and significant impact on repurchase intentions. This shows the quality of service affecting repurchase intention with double mediation of customer satisfaction, and brand trust.Thus, in order to survive and even win the competition in the online marketplace, every online store should ensure the quality of service, satisfaction and trust of customers in order to encourage or strengthen the intention of repurchasing their customers.Keywords: Service Quality, Consumer Satisfaction, Brand Trust, Repurchase intention, Online Store.